Sphagnum subnitens Russow & Warnst. in Tunisia and in North Africa - (:unkn) unknown (My University, 2020)
Sphagnum subnitens Russow & Warnst. is a Suboceanic Boreo-temperate species (Blockeel et al. 2014) known in North Africa, Western Asia, the Azores, Madeira and in most of continental Europe (Hodgetts 2019). Its European distribution shows a slight South-Western tendency being recorded as far south as Andalucia, South Spain and South Portugal (Brugués et al. 2007), Corsica (Sotiaux et al. 2007), Sardinia (Aleffi et al. 2020).
Keywords: African Research